Transparency, Participation, and Village Development: Evidence from Village Fund Management in Prayungan, Bojonegoro - Mufidah , Lailly (Indonesian Journal for Entrepreneurial Review, 2025)
Village Funds (Dana Desa) have become a cornerstone of Indonesia’s decentralization policy, aimed at reducing poverty, promoting equity, and empowering rural communities. Yet, the effectiveness of these fiscal transfers depends not only on financial allocation but also on governance practices, particularly transparency and community participation. This study investigates how these two governance principles influence village development outcomes in Desa Prayungan, Kecamatan Sumberrejo, Kabupaten Bojonegoro. Using a quantitative associative approach, data were collected from 100 respondents, including village officials, community leaders, and residents engaged in financial management and development activities. Multiple linear regression analysis was applied to assess the individual and combined effects of transparency and participation on development outcome. The results show that both transparency and participation have significant positive effects on village development. Transparency in financial reporting fosters accountability and trust, ensuring more efficient allocation of resources. Participation in decision-making and monitoring strengthens legitimacy and sustainability by aligning projects with community needs. Importantly, the combined effect of transparency and participation was found to be stronger than their individual impacts, suggesting that these principles are mutually reinforcing. The findings underscore that fiscal decentralization alone is insufficient without governance mechanisms that empower citizens and hold institutions accountable. Policy implications include the need for more accessible financial reporting, inclusive participation strategies, and stronger oversight to maximize the developmental potential of Village Funds. This study contributes to governance and rural development literature while offering practical lessons for policymakers and communities.